Antiparasitic bromotyrosine derivatives from the caribbean marine sponge aiolochroia crassa (2012)
ABSTRACT: Six bromotyrosine-derived compounds were isolated from the Caribbean marine sponge Aiolochroia crassa: 3-bromo-5-hydroxyO-methyltyrosine (1), 3-bromo-N,N,N-trimethyltyrosinium (2), 3-bromo-N,N,N,O-tetramethyltyrosinium (3), 3,5-dibromo-N,N,Ntrimethyltyrosinium (4), 3,5-dibromo-N,N,N,O-tetramethyltyrosinium (5), and aeroplysinin-1 (6). Structural determination was performed using NMR, MS and comparison with literature data. All isolated compounds were screened for their in vitro activity against Leishmania panamensis, Plasmodium falciparum and Trypanosoma cruzi. Compound 4 showed selective antiparasitic activity against Leishmania and Plasmodium parasites. This is the first report of compounds 1, 4 and 5 in the sponge A. crassa and the first biological activity reports for compounds 2-4. This work shows that bromotyrosines are potential antiparasitic agents.